Flight patterns in zoo‐housed fruit bats (Pteropus spp.). Issue 3 (12th March 2019) - Bell, Edward; Price, Eluned; Balthes, Samantha; Cordon, Matthew; Wormell, Dominic
Abstract: Maintaining the capacity for sustained flight in captivity is a key goal for the management of threatened fruit bats. We developed quantifiable descriptions of flight complexity and used them to assess the suitability of an enclosure for two species of fruit bat of differing size, the large Livingstone's fruit bat, Pteropus livingstonii, and the smaller Rodrigues fruit bat, Pteropus rodricensis, in a two‐part study. In Phase 1, Rodrigues fruit bats flew more often than Livingstone's fruit bats and although the majority of flights in both species were linear, Rodrigues fruit bats were more likely to display complex flight paths involving turns, while flights by Livingstone's fruit bats were more likely to end in a crash‐landing than Rodrigues fruit bat flights. The enclosure may therefore not have been large enough for Livingstone's fruit bats to display a full range of flight behavior over longer distances. In Phase 2, juvenile Livingstone's fruit bats ( < 3 years old) flew more than twice as often as younger adults (3–10 years old) did. Older adult Livingstone's fruit bats over the age of 10 years were not observed to fly. We could not separate out the effects of age, weight and environment during development as these factors were strongly correlated in our study; future work in this area will be very important in understanding the factors that affect flight in captive bats, and how it can be encouraged by appropriate enclosure design. HIGHLIGHTS: Rodrigues fruit bats in a zoo enclosure flew more often and in more complex paths than larger Livingstone's fruit bats. Younger Livingstone's bats flew more than older bats. Enclosure design for captive fruit bats needs to take these factors into account to maintain flight and improve health. Abstract : Rodrigues fruit bats in a zoo enclosure flew more often and in more complex paths than larger Livingstone's fruit bats. Younger Livingstone's bats flew more than older bats. Enclosure design for captive fruit bats needs to take these factors into account to maintain flight and improve health.